Pathways to precarity: Work, financial insecurity and wage dependency among Australia's retrenched auto workers. (June 2021) - Barnes, Tom
Precarious work research has increasingly understood that precarity is not limited to poor job quality. However, this idea has received insufficient attention among older workers whose careers have been erased by retrenchment. The sense in which retrenched workers' lives are co-determined by the residual effects of previous long-term careers has been under-studied. Through a study of the closure of Australia's automotive manufacturing industry, this article shows how workers' life trajectories were differentiated by benefits accrued through their long careers, including union-negotiated redundancy pay and wealth accumulated in home ownership. Retrenched workers adopted different positions on a continuum of wage dependency and household-scale financial security which insulated some from the negative effects of precarious work and relegated others to a pathway of rising precarity. This latter pathway is likely to become more important among older workers due to the disappearance of large-scale manual employment in secure, well-paying jobs.